The Effect of the Use of Video- and Sketch-Based Learning Aids on Increasing Students' Learning Interest: Pengaruh Penggunaan Peraga Pembelajaran Berbasis Video Dan Sketsa Terhadap Peningkatan Minat Belajar Peserta Didik - desvitasari, valestine fitria; Ramli, Muhammad; Sangaji, Faisal (SEARCH: Science Education Research Journal, 2024)
Discussing, watching, and assessing in terms of procedures and results make up the learning process. Learning is the process that benefits the individual participating in it and makes use of the tools and resources that are available to everyone. One of the numerous types of educational media are sketching and video learning. Videos come with a lot of advantages, one of which is their capacity to clarify concepts and procedures related to IPA learning. Techniques from quantitative research are used in the study. The student learning outcomes, student interest scale analysis findings, and observation approaches make up the data gathering process. Following an explanation of how the learning media video was implemented, the pretest result was 65, meaning that it did not meet the minimum requirements for value and learning. The posttest result was 84, meaning that the learning value increased and that it now serves as one of the indicators of students' enthusiasm and interest in continuing their education. Treatment undergoes a substantial shift, and the patient becomes curious in learning via enhanced sketches and video-based instruction.